THE ROLE OF HUMAN RESOURCE MANAGEMENT IN EMPLOYEE CAREER DEVELOPMENT AT PT. MECOSIN INDONESIA - Ardhya, Bella Nanda; Kasiyat, Kasiyat (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This study aims to examine and explain the role of human resource management in employee career development at PT. Mecosin Indonesia. The research method used is a qualitative design with data collection techniques in the form of observation, interviews, and documentation. This research is field research where the problems raised in this study are determined by the problems happening, so this study is qualitative research with a phenomenological approach. This study uses a phenomenological approach where the author will see a reality related to the role of human resource management in employee career development at PT Mecosin Indonesia. To determine the role of human resource management in employee career development, indicators are used; the indicators used include fair treatment in a career, concern for direct superiors, information about various promotion opportunities, interest in being promoted, and level of satisfaction. The role can be defined as a typical behavior that characterizes each person in a workgroup or social context that significantly influences an event. At the same time, career development is a formal effort to improve and add to the abilities that are expected to impact the development and expansion of insight, thus opening up opportunities to get a position or position that satisfies an employee's life. The research results show the role of human resource management in employee career development at PT. Mecosin Indonesia is based on their respective functions, and each line and department has its role and function according to the company's organizational structure